Strategic Human Resource Management In The Age Of Digital Transformation - Anggiat Acnes Nababan; Asron Saputra (International Journal of Education Management and Religion, 2026)
This paper explores the transformation of Strategic Human Resource Management (SHRM) in response to the digital era. The increasing adoption of digital technologies such as Artificial Intelligence (AI), automation, and analytics has significantly reshaped the role of human resources from administrative functions to strategic partners that drive organizational performance. This study discusses how digital transformation influences HR strategies, focusing on digital competencies, employee engagement, and organizational agility. The research highlights best practices in aligning HR strategy with digital innovation to create a sustainable, adaptive, and competitive organization in a rapidly changing environment. The study emphasizes how digital transformation impacts HR strategies and practices, focusing on key dimensions such as digital competencies, employee engagement, organizational agility, and data-driven decision-making. It highlights that SHRM must evolve to integrate technology not only as an operational enabler but as a strategic resource for long-term competitiveness. Through a comprehensive review of recent literature and global best practices from leading organizations, this paper identifies several critical success factors in aligning HR strategies with digital innovation. These include developing a digitally competent workforce, promoting continuous learning, adopting HR analytics for strategic insights, and fostering a culture of adaptability and innovation. The findings underscore that organizations that effectively integrate SHRM with digital transformation initiatives are more likely to achieve sustainable performance, higher employee engagement, and greater resilience in the face of uncertainty. This study contributes to the growing discourse on digital-era human resource management by proposing a strategic framework for transforming HR into a driver of organizational agility and competitiveness in a rapidly changing global environment.